Die noodsaaklikheid vir ’n vak-filosofiese ueskouing van die bedryfsielkunde* - Veldsman, T. H. (Koers, 1982)
The objective of this paper is to outline the necessity for a subject philosophical basis for Industrial Psychology. The paper offers a number of examples of issues which might effect a shift of interest from everyday practice of science to the essential nature of Industrial Psychology as a subject discipline - that is, ultimately, a subject philosophical grounding of Industrial Psychology. The issues that are raised therefore do touch, to a greater or a lesser extent, on the presuppositions on which the subject Industrial Psychology rests.